PEMBERDAYAAN MASYARAKAT BERBASIS EKONOMI WISATA (Studi Kasus Pemberdayaan Perajin Batik Kayu di Desa Wisata Krebet, Desa Sendang Sari, Kecamatan Pajangan, Kabupaten Bantul, Yogyakarta) - , WULANDARI; , Arie Sujito S.Sos M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Village tourism has now developed into a tourist attraction visited by many people . The advent of the tourist village communities due to the potential that can be managed into a tourist attraction . In this study , a tourist village which made the object of a tourist village in which there are wooden batik as towing tourists . Village Tourism Krebet made through the presence of the community empowerment . This study describes the empowerment wooden batik artisans in the village of Tourism Krebet the role of the three actors of development . The three actors , namely government , private and public . Researchers want to show the results of such empowerment can improve the economy if the wood batik artisans . This study describes the development of the Tourism Village Krebet related to the presence of social capital in the community . This research was conducted using a qualitative case study approach . Case study approach is used to show the uniqueness of the Village Tourism Krebet who has a lot of tourism potential , one wooden batik . In this study involves the Tourism Village craftsmen and managers Krebet as informants . Data was collected through observation , interviews and field documentation . After getting enough data , researchers used a qualitative descriptive analysis . Qualitative description is divided into three steps , namely data reduction , data display and conclusion . Then used data triangulation techniques to examine the validity of the data obtained . Based on the research conducted , showed that of empowerment has brought many changes for the people of the village of Tourism Krebet especially for wooden batik artisans . Empowerment Efforts have been able to increase the economic income of wooden batik artisans . Empowerment efforts as well as a promotional event for wooden batik . Then more and more orders batik wood and expanded marketing area outside Yogyakarta and abroad. ability to make wooden batik artisans also increased with many variations of wooden batik works in a variety of forms . However , this empowerment does not eliminate the element of social capital has Krebet Tourism Village community . Dominant society by craftsmen , not make people Krebet split Tourism Village . Instead , the public is not craftsmen and artisans come together to promote Rural Tourism Krebet . This is demonstrated by the many growth experienced Krebet Tourism Village . Not only the wooden batik , but also manages natural attractions like Canyons Pulosari . Then also try to help people instead of craftsmen that sugar makers to increase the variation in sales . Thus , development of Rural Tourism Krebet wider benefits , not only in the batik artisans of wood but the entire community Krebet Tourism Village .